AS A FACTOR OF INTERDISCIPLINARY INTEGRATION-EDUCATIONAL EFFICIENCY IN PRIMARY GRADES (CAHIERS MAGELLANES-NS, 2024)
In the article, the practical importance of the mutual integration of subjects in the educational system, the advantages and disadvantages of establishing integrated education in primary grades, the general characteristics of the integrated lesson, the experience organized using integrated technologies in the educational process test works and its results are described.